A taste of their own medicine: Guideline adherence and access to expertise - Amy Finkelstein; Petra Persson; Maria Polyakova; Jesse M. Shapiro (Research Institute of Industrial Economics (IFN), 2021)
We use population administrative data from Sweden to study adherence to 63 medication-related guidelines. We compare the adherence of patients without personal access to medical expertise to the adherence of those with access, namely doctors and their close relatives. We estimate that, among observably similar patients, access to expertise is associated with 3.8 percentage points lower adherence, relative to a baseline adherence rate of 54.4 percent among those without access. This association is larger for recommendations with a weaker clinical motivation. Our findings suggest an important role in non-adherence for factors other than those, such as ignorance, complexity, or failures of patient-provider communication, that would be expected to diminish with access to expertise.
Keywords: D83; I12; I18; 330; Information; Medical decision-making; Experts